Quality of life among patients with diabetic neuropathy pain in HTAA - Al-Mahmood, Sinan; Yahaya, Nurul Nadia (2014)
The researchers related to diabetic neuropathy pain issues are still very limited. The issues had been discussed mostly on the internet, but it is hard to find the article journal about this issue locally even though the cases of amputation among diabetic patient increasingly until today in this society. Diabetic patients suffering from painful diabetic neuropathy pain (DNP) or more commonly referred to as diabetic nerve pain, often remain untreated. Due to the challenges in diagnosing DNP, patients learn to familiarize to living with their pain. Twenty percent of diabetic patients suffers from this complaint, and the prevalence of this condition continues to rise. The aim of this study is to determine the condition of life among diabetic patients with diabetic neuropathy pain. Pain controlling allows patients with this condition to improve their quality of life.The study is conducted in the outpatient setting and medical ward in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. A total of 90-diabetic patients were diagnosed with diabetic neuropathy pain symptoms by using the Audit of Diabetes-Dependent The quality of Life (ADDQoL) instrument and DN4. The findings showed that diabetic patients with diabetic neuropathy pain have a poor quality of life 90% (n=81) whereas 10% (n=9) respondents are with good quality of life. By identifying the quality of life of diabetic patients with diabetic neuropathy pain, authorities (government and nongovernment organization- NGO) could take many approaches to the diabetic patients in dealing with this issue by recognizing the personal, public and economic burden of chronic pain and establish chronic pain as a priority public health concern in Asia Pacific.